A bivariate life distribution and notions of negative dependence. Issue 1 (30th April 2020) - Bhuyan, Prajamitra; Ghosh, Shyamal; Majumder, Priyanka; Mitra, Murari
Abstract : Bivariate life distributions used to model negative dependence typically possess certain limitations; in particular, the correlation coefficient takes values in a restricted subrange of [ − 1, 0 ] . We construct a new bivariate life distribution to remedy this. Properties of the proposed distribution are studied. It is shown that the distribution satisfies most of the popular notions of negative dependence prevalent in the literature. Stress–strength reliability bounds are obtained, and parameter estimation methodology has been discussed. Performance of the estimators are compared through a simulation study.